Expression Of Tumour Markers And Determination Of Microvessel Density In Mnu-Induced Breast Tumour - Mohd Nafi, Siti Norasikin (2009)
Angiogenesis plays an important role in breast tumour development. In this study, breast tumours were induced by injecting rats intraperitoneally with 1-methyl-1-nitrosurea (MNU) at dose of 70 mg/kg body weight in 3 consecutive days into 21-days old rats. Angiogenesis memainkan peranan penting dalam perkembangan tumor payudara.Untuk kajian ini, pengaruhan tumor payudara dilakukan melalui suntikan karsinogen MNU (1-methyl-1-nitrosurea) pada tikus berumur 21 hari.